Postgraduate Dental Students, Perceptions of the Educational Environment in Dental School, Babol University of Medical Sciences according to DREEM Model - Mina Motallebnejad; Ali Asghar Bayani; Soraya Khafri; Fatemeh Gilchini (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE:Educational environment is a portion of lesson plan which can affect on different aspects of training in the schools. The aim of the present study is assessment of educational environment at dental school of Babol University of Medical Sciences based on trainee's attitude evaluated by DREEM model. METHODS:The present research is a descriptive cross-sectional survey that accomplished during 2 years among postgraduate students which entered to dental school in the years 2009-2012. The questionnaire consisted of 2 parts: general information and DREEM questionnaire with 50 questions in 5 recognition fields (i.e., learning, teachers, self recognition of scientific ability, educational environment and social position). Data were analyzed with SPSS18 by statistical tests like T-test and Anova, mean and SD were measured for each variable. FINDINGS:According to DREEM, the perception of postgraduate dental students was desirable ( 114.53±16.86) .It was not associated to gender and the enterance year of the students. In" student,s perception of teacher" Oral Pathology and Dental Prosthetics departments had the highest and the lowest scores, respectively. In "student,s social self- perceptions" Oral Pathology and Orthodontics departments had the highest and the lowest scores, respectively. Educational environment was nearly the same in different departments of this school. CONCLUSION:Regarding to our findings educational environment was "desirable" and it was almost the same in all departments of dental school, but, paying more attention to some domains such as "student,s perception of teachers" and "student,s social self- perception" in some departments is necessary.